Implementation of sharia contracts at Bank Syariah Indonesia Branch Office Malang Suprapto - Nugroho, Tri Sulistyo (Maliki Interdisciplinary Journal, 2023)
Finance is one of the most important elements in life. The financial aspect is always present in various aspects of our lives, starting from health aspects, meeting daily needs, trading, there are always transactions involving money in it. From this, banking needs to be present in our lives, especially for the economy. In general, there are 2 types of banking in this world, the 2 types of banking are conventional banking and Islamic banking. In this article, the author would like to review the application of fiqh aqad at Bank Syariah Indoensia especially at the Malang Suprapto branch office.